PARAMETER OPTIMIZATION FERMENTATION FOR BIOMASS FORAGE CROPS IN DEVELOPED WITH YEAST BATCH ON OIL AND WHEY DESPROTEINIZED - Flores P., Abad (2008)
This work was carried out with the purpose to optimize physical chemical parameters obtain a microbial biomass from Kluyveromyces marxianus NRRL –Y-1109 y Candida pseudotropicalis BT-UNMSM_6 . The yeasts were grown on sweet whey crude and deproteinized, supplemented with nitrogen and vitamins sources. The optimization of fermentation parameters was obtained applying a Taguchi´s factorial design. It was established as optimal conditions: An pH 4.5; Temperature 30 °C and an aeration rate of 1.475 VVM; Agitation speed 600 RPM, Lactose concentration 5 g/L; (NH4)2S04 6 g/L; Yeast extract 1.5 g/L . The average biomass yield obtained was 0.56 g/g lactose and 0.54 g/g Lactose for K. marxianus and C. pseudotropicalis respectively grown on sweet whey deproteinized diluted 50%, and Cellular yield 0.405 g/g with K. marxianus NRRL-Y-1109 and Yx/s 0.38 g/g with Candida pseudotropicalis grown on sweet whey crude. A lactose consumption of 98.25 & 94.45% and a cellular concentration of 12.75 g/L & 12.52 g/L respectively at the end of the fermentation.